Rural-urban migration of young people and adolescents at risk of social and educational exclusion - Cotrado, Bethzabe (2019)
This article makes a review of scientific literature with the objective of knowing the different perspectives and interpretations on rural - urban migration of young people and adolescents at risk of social exclusion. The methodology applied in the framework of the qualitative approach allowed the organization, study and interpretation of 25 research published in the digital library of the Autonomous University of Barcelona. As a result, it was understood that migration is a complex, dynamic and multifaceted phenomenon. In this perspective emerges the type of rural-urban migration movement that falls on the group of young people and adolescents who "go out in search of work" and those who "migrate to study". This population of migrant youth and adolescents from the countryside to the city is one of the most vulnerable segments. In this condition, young subjects are exposed to multiple dynamic processes of social, educational, labor, political and cultural exclusion.